The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1051/fruits/2014010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of storability and quality maintenance of carambola (Averrhoa carambolaL.) fruit by using composite edible coating

Abstract: Enhancement of storability and quality maintenance of carambola (Averrhoa carambola L.) fruit by using composite edible coating. Abstract-Introduction. Our investigation aimed to examine the influence of eco-friendly edible coatings composed of sodium alginate, olive oil and green tea extract (GTE) on improving the shelf life and nutritional quality of carambola (A. carambola L.). Materials and methods. The combinations and concentrations of composite coatings tested were (2% sodium alginate + 0.1% olive oil) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Slower decline in acidity in treated fruits compared to control might be due to delayed senescence and lower respiration rate in the fruits. Similar observations were also reported by Iqbal et al, 2017 in sweet orange and Baraiya et al, 2014 in carambola who also observed that coated fruits showed less reduction in acidity content during storage period. The data related to the effect of composite coatings during storage period on ascorbic acid of guava fruits cv.…”
supporting
confidence: 90%
“…Slower decline in acidity in treated fruits compared to control might be due to delayed senescence and lower respiration rate in the fruits. Similar observations were also reported by Iqbal et al, 2017 in sweet orange and Baraiya et al, 2014 in carambola who also observed that coated fruits showed less reduction in acidity content during storage period. The data related to the effect of composite coatings during storage period on ascorbic acid of guava fruits cv.…”
supporting
confidence: 90%
“…In general, lower pH values were observed in the coated starfruits compared to control. This was due to the fact that the coatings were able to reduce the respiration and metabolic rates, hence decreasing the uptake of organic acids in the respiration process ( Baraiya et al., 2013 ). Thus, the application of coating slowed down the pH changes of the fruit.…”
Section: Resultsmentioning
confidence: 99%
“…Edible coating is environmentally friendly and can provide additional protective layers to fruits. Several studies have been conducted to develop a method to prolong the shelf life of starfruits, including edible coating ( Baraiya et al., 2013 ; Gol et al., 2013 ; Mohamad Zaki et al., 2012 ). In general, coating can minimize moisture loss, respiration, and transpiration rate, as well as maintaining a fruit's firmness ( Mannozzi et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous study conducted on strawberries coated with chitosan showed higher antioxidant activities compared to untreated fruit (Wang and Gao 2013). The application of green tea extract along with alginate coating was found to be effective in improving the level of phenolic compounds and ascorbic acid (Baraiya et al 2014).…”
Section: Total Antioxidant Activitymentioning
confidence: 96%